Arsenic removal from highly contaminated groundwater by iron electrocoagulation: investigation of process parameters and iron dosage calculation - Müller, Daniel; Stirn, Charlotte; Maier, Martin V. (Water, 2021)
Electrocoagulation (EC) is gaining increased attention for water treatment as it efficiently removes various water contaminants. Therefore, EC was applied to remove arsenic from groundwater of a highly contaminated site in Hamburg, Germany. Groundwater containing 3250 and 14,600 µg/L arsenic, mainly as Arsenite (As(III)), was treated in three different EC batch reactors using a monopolar parallel electrode-configuration. This study focused on iron EC with constant current densities and variable voltage, to investigate the influence of current density, surface to volume ratio, initial arsenic concentration and water volume on the removal of arsenic and the influences on the groundwater composition. Arsenic removal >99.9% was achieved for configurations with high iron dosage after four hours of EC treatment. German drinking water standard for arsenic (<10 µg/L) was obtained after around two hours depending on the applied current densities. Arsenic removal efficiency shows independence from current density, surface to volume ratio, initial concentration and water volume, with respect to the calculated iron dosage. Consequently, the dimensioning and regime of efficient operation of the EC reactor for arsenic removal from groundwater can be calculated solely from the iron dosage determined by the applied current.